Synthesis, characterization and application of a novel ion hybrid imprinted polymer to adsorb Cd(II) in different samples - Adauto, Anais (2020)
Two new ionic imprinted hybrid polymers (IIHP) and their corresponding non imprinted hybrid polymers (NIHP) were synthesized. The prepared IIHP was highly selective to Cd2+. To prepare the IIHP, 1-vinylimidazole (VIN) was used as the functional monomer, (3-mercaptopropyl) trimethoxysilane (MP) or (3-aminopropyl) trimethoxysilane (AMP) was used as the functional organosilane, trimethylolpropane (TRIM) was used as the crosslinking agent, AIBN was used as a radical initiator and TEOS was used as a functional precursor. The functional monomer was selected considering calculations based on the density functional theory (DFT). The fabricated materials were characterized via field emission gun scanning electron microscopy (FEG-SEM), Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDX) and thermogravimetric analysis (TGA). The maximum adsorption capacity of Cd2+ was achieved at a pH of 7.2 in the tris-HCl medium. The adsorption test indicated that the reaction followed pseudo second order kinetics, and the equilibrium sorption data fitted well into the Langmuir isotherm model. The relative selectivity coefficients of polymers IIHP-VIN-AMP and IIHP-VIN-MP, as evaluated in binary mixtures of Cd2+ and interferent cations (Pb2+, Zn2+, Hg2+, Cu2+, Ni2+, Ca2+, Mg2+, and Na+) at different molar ratios, were greater than one due to the presence of specific recognition sites for Cd2+ ions. Moreover, the selective materials exhibited a high reusability and reproducibility in the context of Cd2+ adsorption. These adsorbent materials, specifically IIHP-VIN-MP, exhibited a % removal efficiency of more than 90% for the Cd2+ in river water samples.